Nano-bio-layers on Ti6Al4V alloys using electrophoretic deposition (EPD) for orthopaedic applications - Kaya, Cengiz (CARL HANSER VERLAG, 2007)
A novel, cost-effective and fast method based on electrophoretic deposition (EPD) was employed to produce nano-structured bio-active layers of hydroxyapatite (HA) on Ti-based metallic implants for orthopaedic applications. Nano-size HA powders were first synthesised using sol-gel technique and kinetically stable colloidal suspensions that contain HA powders were prepared for coating experiments using EPD. Ti6Al4V metallic alloys were coated using different processing parameters, such as deposition time and voltage to optimise coating thickness and eliminate crack formation on the surface. Different coating thickness from 10 mm to 60 mm were achievable under controlled parameters. It was showed that sintering temperature of HA layers was lowered to 500 degrees C by using sol-gel synthesised ultra-fine (30-40 nm) HA starting powder during EPD. The thickness of the coating layers plays an important role to obtain deposits with free of cracks. EPD-formed layers up to 25 mm thickness contain no cracks on the surface but above this thickness extensive cracks are seen within the deposit. Lower sintering temperatures form stoichiometric HA with no other phases and this low temperature should contribute to minimised residual stresses within the metallic alloy which means lifetime of the metallic implant will be longer. Overall, a completely new method of making nano-bioactive-ceramic layers which results in the formation of thin and thick films with controlled microstructures and phase distribution on Ti6Al4V metallic implants was introduced.
Keywords: CERAMIC COATINGS; MATRIX COMPOSITES; FABRICATION; Materials Science